Does size of banks really matter? Evidence from CDS market data - İlker Arslan (Izmir University of Economics, Department of Economics, 2010)
In this study we try to find that whether markets take into account the phenomenon of Too Big to Fail. With the help of CDS market data, which reflects the risk, markets attribute on banks, we calculate the default probabilities of banks in one, two, and three years. Then we regress these results with financial values like total assets, total shareholders' equity and net income. Later on we extend our study and repeat our regression analysis using Return on Assets as dependent variable. We find that markets give more importance to profitability of a bank than its size when pricing the riskiness of the bank. We conclude that Too Big to Fail is not a valid term as thought but may be Too Profitable to Fail may be better.
Keywords: G21; G28; 330; Kreditderivat; Bankrisiko; Betriebsgröße; Rentabilität; Bankgeschäft; Welt